A Generation Z and the Challenge of Toxic Leadership: Between Wellbeing, Productivity, and Loyalty - Andriani, Helma Putri; Aini; Chaniago, Harmon (Asosiasi Ahli Administrasi Indonesia, 2025)
The presence of Generation Z in the workforce has shifted expectations toward empathetic, transparent, and emotionally supportive leadership. This quantitative study examines the influence of toxic leadership on psychological well-being, productivity, and work loyalty among 50 Generation Z employees working across various sectors in Bandung. Data were collected via questionnaires and analyzed using multiple linear regression with SPSS. Results show that toxic leadership marked by authoritarian, manipulative, unsupportive, and unempathetic traits significantly reduces psychological well-being, as reflected in higher stress and job dissatisfaction. In contrast, its impact on productivity and loyalty was not statistically significant, explaining only 3 percent and 6.4 percent of the variance, respectively. Nonetheless, a negative directional trend was noted, indicating potential declines in motivation and morale. The study's novelty lies in its focus on Generation Z in Bandung, a city marked by rapid urbanization, creative industries, and a high concentration of young professionals. This provides a unique generational and cultural lens often underrepresented in toxic leadership research. Theoretically, this study enriches the discourse on destructive leadership by highlighting its differential effects on psychological versus behavioral outcomes. Practically, it underscores the need for organizations to adopt more empathetic and adaptive leadership styles to build a healthier, more inclusive, and sustainable work environment for the emerging workforce.